The influence of recycled plastics added via the dry process on the properties of bitumen and asphalt mixtures - Miranda, Henrique M. Borges (2023)
Nowadays, the use of recycled plastics is gaining momentum, especially after the 2017 plastics crisis, and the asphalt pavement industry has positioned itself as a leader due to its long history of using recycled materials. However, regardless of the potential interest in using recycled plastics in road infrastructure, there is still a lack of knowledge on how to make their incorporation into asphalt mixtures a daily practise. For this reason, a study was conducted to evaluate the influence of five patented recycled plastics: on bitumen properties, on the affinity between aggregate and bitumen, on the resistance of five asphalt mixtures (AC14 surf) to permanent deformation and moisture, and on their skid resistance. The recycled plastics used consist mainly of PE (low and high density) and PP and were added via the dry process due to the simplicity and low cost of the process. Results show that recycled plastics influence bitumen properties, but do not improve ageing resistance. In addition their use tends to improve the affinity between aggregate and bitumen and influence the behaviour of asphalt mixtures: specimen porosity is increased, Marshall properties generally remain similar or increase slightly, water sensitivity is not significantly affected or slightly improved, and surface properties remain similar for macrotexture and exhibit higher slip/skid resistance. No significant relationship was found between bitumen properties and other properties studied. Regardless of the type, form, plastic content, replacement, or increase in bitumen content used in this study, recycled plastics are an alternative t6o other techniques for pavement construction/ rehabilitation.